The choice: violence or poverty. (2nd October 2022) - Summers, Anne
ABSTRACT: How to reduce the incidence of domestic violence continues to challenge policymakers in Australia. This article draws upon a Keynote Address delivered at a University of Technology Sydney Symposium on gender equality, domestic violence and work. Through presenting ground-breaking data on domestic violence in Australia, I show the stark situation many women face in Australia – to stay with violent partners or leave a violent relationship and risk poverty. Domestic violence often has immediate and longer-term consequences for employment with as many as 50% of women facing lower incomes and cash flow problems. Existing government policy is inadequate, with a phenomenon of 'policy-induced poverty' arising for many women who leave violent relationships. Further research and policy development is required to not only understand the work and employment consequences for women experiencing domestic violence, but examine ways in which policy can be improved to support victims of violence.